Robotic dry cleaner for photovoltaic solar panels: an implemented design that evaluated in iraq's weather - Mahmood H. Salman; Ahmed J. Abid; Adel A. Obed (Universitas Ahmad Dahlan, 2021)
Arabian desert areas are suffered from high mitigation in the produced photovoltaic (PV) power due to high dusty weather. This article presents a robotic cleaner that will significantly reduce the impact of dust on the installed PV systems in these areas. The proposed robotic cleaner is simple, low cost, standalone, self-powered, portable, and connected to the cloud. ESP32 used as a controller that manages the cleaning process and monitors its PV power production, the battery's state of charge, time of the day, and weather conditions. Thanks to the ESP32 features and its ability to connect to the cloud, as an internet of things (IoT), via the ThingSpeak website. All the electrical, mechanical, and electronic design aspects are presented and implemented in this article. The results show the effectiveness and performance enhancement due to periodic cleaning using the proposed robotic cleaner. The results also show that the total percentage of the monthly normalized accumulated losses for the two scheduled cleaning photovoltaic strings with a performance improvement of 15.54% for the weekly cleaned string (WCS) 83.04% for the never cleaned string (NCS) through the tested month.